2011
DOI: 10.3155/1047-3289.61.5.535
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Transference Rules for Bromine in Waste Printed Circuit Boards during Microwave-Induced Pyrolysis

Abstract: The production of waste printed circuit boards (WPCBs) has drawn increasing global concern, especially because the high bromine (Br) content (5-15%) places obstacles in the way of simple disposal techniques. Microwave-induced pyrolysis of WPCBs provides a promising way to dispose of these hazardous and resource-filled wastes. The transference rules for Br during microwave-induced pyrolysis have been investigated experimentally. It was found that the microwave energy could be used more efficiently to accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…10,[17][18][19][20] Our working group is just carrying out research on the recycling of electronic wastes through microwave processing and find that microwave-induced pyrolysis combined with a featured mechanical processing is a very efficient way to recycle these wastes. [21][22][23][24] In our studies, the organic compositions in electronic wastes can be recycled in the form of energy and the metals can be effectively recovered.…”
Section: Introductionmentioning
confidence: 99%
“…10,[17][18][19][20] Our working group is just carrying out research on the recycling of electronic wastes through microwave processing and find that microwave-induced pyrolysis combined with a featured mechanical processing is a very efficient way to recycle these wastes. [21][22][23][24] In our studies, the organic compositions in electronic wastes can be recycled in the form of energy and the metals can be effectively recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has studied the heating effects associated with microwave-metal discharges and found that the energy conversion ratio from electrical energy to heat can reach as high as 30% [28]. Based on the unique material characteristics of WPCBs and the discharge properties of metals, we have previously established that microwave-induced pyrolysis holds promise as a way to process WPCBs [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that because of the selective characteristic, the microwave induced pyrolysis may be applied in an energy efficient way for PCB waste heat treatment. Application of some strong microwave absorbers may expedite the pyrolysis process by rapid heating [20]. Current studies present the inter-comparison studies with respect to the PCB waste characterization using microwave and resistive heating in order to understand the nature of volatiles and residue obtained during the two different heating processes.…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 99%